UDE Based Robust Control of Grid Tied Inverters - Akın USLU (International Journal of Applied Methods in Electronics and Computers, 2020)
In this paper, a modified (proportional-integral) PI control is suggested to improve current tracking performance of three-phase grid-tied inverters (GTI). Presence of the L filter between inverter and grid, makes complex to design a controller with proper parameters, due to characteristics of the filter. Clasical PI control depends on an accurate dynamical model, thus its performance is deteriorated by parametric uncertainties, unmodelled dynamics and external disturbances, when operating conditions affect the filter parameters. To solve this problem, uncertainty and disturbance estimator based PI current control approach is proposed for grid-tied inverters, which provides robustness against to parametric perturbations. An UDE based observer that has been adopted into the PI current loop is used to eliminate lumped disturbances and the steady-state tracking error of current states, which can enhance the robustness of the control performance. Then, parameter design method, stability and robustness analysis are explored and presented. Performance comparison among the clasical PI and proposed control scheme. Efficacy and performance of the proposed approach are carried out by simulations and experiments. Experimental results show that effectiveness of the suggested control method against parametric uncertainties and disturbances are succesfully validated. Besides, the precise current tracking performance with zero steady state error has been reached.